ISLAMISASI DI RIAU - Ellya Roza; Yasnel Yasnel (State Islamic University Sultan Syarif Kasim, 2016)
Islamization is a process in which someone is invited to apply Islamic teachings purely in all aspects of life such as religious ritual, economic, social and cultural, politics, law and governance. The existence of cemetery of Syekh Burhanuddin and all its historical story are evidences that Islam exists in Kuntu which also influence others region in Riau for its religion, culture, social, and so on. From the investigation, historically, in Riau, Syekh Burhanuddin - a famous Islamic Arabian preacher has come to Kuntu and developed Islam. The Islamic teachings delivered by Syekh Burhanuddin remains well in the society until today. He spread Islam and its teachings peacefully, like others preachers of Islam do generally. The way of Syekh Burhanuddin delivered the Islamic teachings and its contents influenced the culture and characters of people in Kuntu, Riau or Indonesian people in general.